(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1859)
The article describes a three-storey house in Culross in which he found eighteen illustrated panels and morality verses. The author notes that the room he found this decoration in has significant damage from damp, so he presents the text of the verses to preserve their contents. The article concludes with a history of the Bruce family, who most likely built the house, and its association with King James I and VI. When this paper was presented to the Society, John Stuart added that it might be helpful to create a directory of inscriptions found in castles across Scotland and offers some examples from different parts of the country.